Tenofovir alafenamide after switching from entecavir or nucleos(t)ide combination therapy for patients with chronic hepatitis B. (30th April 2020) - Ogawa, Eiichi; Nomura, Hideyuki; Nakamuta, Makoto; Furusyo, Norihiro; Koyanagi, Toshimasa; Dohmen, Kazufumi; Ooho, Aritsune; Satoh, Takeaki; Kawano, Akira; Kajiwara, Eiji; Takahashi, Kazuhiro; Azuma, Koichi; et al.
Abstract: Background and aims: Tenofovir alafenamide (TAF) has been newly approved for the treatment of chronic hepatitis B (CHB). We aimed to assess the effectiveness and renal safety of switching from entecavir (ETV) or nucleos(t)ide analogue (NA) combination therapy to TAF. Methods: This multicentre, retrospective, cohort study included 313 consecutive CHB patients who switched to TAF monotherapy after treatment with ETV or a nucleos(t)ide analogue (NA) combination for over 2 years. Virological/laboratory responses were evaluated for 48 weeks after switchover. Chronic kidney disease (CKD) was defined as an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 . Differences in longitudinal parameters were compared by the generalized estimating equation method. Results: In the prior ETV group (n = 191), the HBV DNA suppression rate at week 48 was significantly increased, from 75.9% to 96.9% ( P  < .001). Additionally, mean changes in the HBsAg level at week 48 in HBsAg ≥ 3.0 logIU/mL and < 3.0 logIU/mL groups were −0.09 and −0.13 logIU/mL respectively. In the prior NA combination group (n = 122), the mean changes in HBsAg level at week 48 in the HBsAg ≥ 3.0 logIU/mL and <3.0 logIU/mL groups were −0.08 and −0.11 logIU/mL respectively. For patients with CKD, the eGFR at week 48 was significantly improved compared to those with non‐CKD (adjusted slope coefficient difference: 2.75 mL/min/1.73 m 2 /48 weeks; P  = .001). Conclusions: Switching from ETV or an NA combination to TAF was effective for HBV suppression and continued HBsAg reduction. Moreover, the renal glomerular function of patients in the prior NA combination group with CKD was significantly improved compared to those with non‐CKD. LAY SUMMARY: Nucleos(t)ide analogues, such as entecavir, tenofovir disoproxil fumarate and tenofovir alafenamide, inhibit hepatitis B virus (HBV) replication and are recommended as first‐line oral agents for chronic HBV infection. We evaluated the virological/biochemical effects and renal safety when patients are switched from entecavir or nucleoside‐nucleotide analogue combination therapy to tenofovir alafenamide. Our findings suggest that switching to tenofovir alafenamide was effective for HBV suppression and the improvement in renal function for patients with chronic kidney disease.